2015
DOI: 10.1503/cjs.016414
|View full text |Cite
|
Sign up to set email alerts
|

Initial assessment of patient handoff in accredited general surgery residency programs in the United States and Canada: a cross-sectional survey

Abstract: Background: Communication errors are considered one of the major causes of senti nel events. Our aim was to assess the process of patient handoff among junior surgical residents and to determine ways in which to improve the handoff process. Methods:We conducted nationwide surveys that included all accredited general surgery residency programs in the United States and Canada.Results: Of the 244 American and 17 Canadian accredited surgical residency pro grams contacted, 65 (27%) and 12 (71%), respectively, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 12 publications
0
14
0
1
Order By: Relevance
“…To illustrate, 80% of severe medical errors were attributed to miscommunication during handoffs (Joint Commission, 2012b). Specifically, poor communication during handoffs can lead to delayed and missed diagnoses (Lorincz et al, 2011), litigation and malpractice claims (Gandhi et al, 2006; Singh, Thomas, Petersen, & Studdert, 2007), omitted patient information (Devlin, Kozij, Kiss, Richardson, & Wong, 2014), diagnostic testing errors (Murphy, Singh, & Berlin, 2014), treatment delays (Horwitz, Moin, Krumholz, Wang, & Bradley, 2008), patient harm (Arora, Johnson, Lovinger, Humphrey, & Meltzer, 2005; Kitch et al, 2008; Saleem, Paulus, Vassiliou, & Parsons, 2015), and mortality (American Thoracic Society, 2016). Despite handoffs being vulnerable to communication breakdowns, they are an essential, frequent part of routine medical care.…”
Section: Introductionmentioning
confidence: 99%
“…To illustrate, 80% of severe medical errors were attributed to miscommunication during handoffs (Joint Commission, 2012b). Specifically, poor communication during handoffs can lead to delayed and missed diagnoses (Lorincz et al, 2011), litigation and malpractice claims (Gandhi et al, 2006; Singh, Thomas, Petersen, & Studdert, 2007), omitted patient information (Devlin, Kozij, Kiss, Richardson, & Wong, 2014), diagnostic testing errors (Murphy, Singh, & Berlin, 2014), treatment delays (Horwitz, Moin, Krumholz, Wang, & Bradley, 2008), patient harm (Arora, Johnson, Lovinger, Humphrey, & Meltzer, 2005; Kitch et al, 2008; Saleem, Paulus, Vassiliou, & Parsons, 2015), and mortality (American Thoracic Society, 2016). Despite handoffs being vulnerable to communication breakdowns, they are an essential, frequent part of routine medical care.…”
Section: Introductionmentioning
confidence: 99%
“…Surgical members, particularly fellows and residents seemed unsure about their role during the handover, about what was expected, or what information they needed to provide. Findings from Saleem, Paulus, Vassiliou and Parsons (2015) suggest that the majority (77-96%) of general surgical residents, in the American and Canadian residency program, do not receive any training on patient handover prior to starting their surgical residency. Participants in this study shared similar concerns and discussed lack of role modeling and handover training in the medical curriculum.…”
Section: Ownershipmentioning
confidence: 99%
“…Thus, handoff training program must be continually conducted to perform a consistent patient handoff [1]. [6] reported that handoff process supervision can improved handoff consistency.…”
Section: Staff Education and Handoff Trainingmentioning
confidence: 99%
“…Errors in handoff process can lead to communication failure that can impact to missing transfer information and resulted in patient's harm. Barriers in handoff process must be addressed to improve the quality of the process.The most common reason for incomplete patient handoff that resulted in minor and major harm was that the verbal handoff received didn't contain the most current information about the patient[6]. Inaccurate information in handoff process can be resulted from human factors (knowledge, culture, fatigue), organization culture (lack of teamwork and leadership, blaming culture), lack of training, no standardized tools, patient-related factors, and environment (chaotic environment, noise, high risk and high volume environment, numerous of comorbid conditions)[4,5].…”
mentioning
confidence: 99%
See 1 more Smart Citation